PENGARUH LOAN TO DEPOSIT RATIO, CAPITAL ADEQUACY RATIO, RETURN ON ASSET DANNON PERFOMING LOAN TERHADAP RETURN SAHAM - Sri Ayem; Sri Wahyuni (Jurnal Akuntansi, 2017)
This study aimed to examine the effect Loan to Deposit Ratio (LDR) , Capital Adequacy Ratio (CAR) , Return on Assets (ROA) and Non -Performing Loans (NPL) on stock returns banking companies listed in Indonesia Stock Exchange . The Independent variable used is the Loan to Deposit Ratio (LDR) , Capital Adequacy Ratio (CAR) , Return on Assets (ROA) and non- performing loan (NPL) dependent variable stock returns . The purpose of this study was to obtain empirical evidence about the influence of Loan to Deposit Ratio (LDR) , Capital Adequacy Ratio (CAR) , Non Performing Loan (NPL) and Return on Assets (ROA) on stock returns banking companies listed in Indonesia Stock Exchange . The population in this study is a banking company that is listed on the Indonesia Stock Exchange (IDX) the observation period 2008 to 2012 . Data used in this study was obtained from the Bank's Financial Statements obtained from the website of the Indonesia Stock Exchange and Bank Indonesia . Data analysis method used is multiple linear regression , hypothesis testing while using the simultaneous test ( F test ) to test the effect of these variables together and t test with a significance level of 5 % to test the effect of partial variables . Based on the test results , the results obtained simultaneously Loan to Deposit Ratio (LDR) , Capital Adequacy Ratio (CAR) , Return on Assets (ROA) and Non -Performing Loans (NPL) effect on stock returns in banking companies listed in Indonesian Stock Biursa , while partially Loan to Deposit Ratio (LDR) has a positive effect is not significant , its capital adequacy ratio (CAR) and Return on Assets (ROA) and a significant positive effect of Non performing loan (NPL) significant negative effect on stock returns in corporate banking . Predictive ability of the four variables on stock returns is 57.1 % , as indicated by the adjusted R2 , while the rest is influenced by other factors not included in our model . Keywords: stock return, Loan to Deposit Ratio, Capital Adequacy Ratio, Return on Assets, Non-performing loan